Mission hurricane / Doublecross. - Goebel, Jenny (39 clues. Doublecross, 2016)
Siblings Dan and Amy Cahill have managed to avert one disaster recreation threatened by the man who calls himself the Outcast, but they have mere days to learn where the Outcast will strike next. The clues are pointing them toward a disaster modeled after Hurricane Katrina.